2018
DOI: 10.1556/018.69.2018.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the formation of amyloid-like fibrils using herbal extracts

Abstract: We tested the amyloid fibril formation inhibitory effect of seven teas diluted in 55% ethanol at pH 7.0 at a protein concentration of 0.15 mg/ml α-chymotrypsin. In the experiments we investigated the formation and inhibition of amyloid fibrils by turbidity measurements, aggregation kinetics experiments and Congo red binding assay. The results suggest that the different teas effectively inhibit the formation of amyloidlike fibrils. The two most potent inhibitors were peppermint and melilot, extracts which almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…As seen in Figures 2A,B, 3A, insulin samples treated with cyanine dyes at low dye-protein ratio 0.5, showed 2-28 times lower ThT fluorescence intensity (coupled with much smaller turbidity) than a control sample (not containing the cyanine dye), that displayed the largest ThT fluorescence response and the highest turbidity [55,56]. Accordingly, the kinetic parameters of the protein fibrillization significantly differ from those of the control sample, reflecting the inhibition of the protein aggregation (Table 1).…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…As seen in Figures 2A,B, 3A, insulin samples treated with cyanine dyes at low dye-protein ratio 0.5, showed 2-28 times lower ThT fluorescence intensity (coupled with much smaller turbidity) than a control sample (not containing the cyanine dye), that displayed the largest ThT fluorescence response and the highest turbidity [55,56]. Accordingly, the kinetic parameters of the protein fibrillization significantly differ from those of the control sample, reflecting the inhibition of the protein aggregation (Table 1).…”
Section: Resultsmentioning
confidence: 88%
“…The coincubation of trimethine/pentamethine/heptamethine compounds with the insulin samples resulted in a rise of both lag time, up to 7.5 times (suppressed nucleation) and k , up to 3.2 times (enhanced elongation) compared to the control values, with the exception of AK3-5, AK5-3, AK5-9, which retarded the elongation and slowed down the nucleation of insulin fibrils. Notably, the experimental conditions affecting the nucleation and elongation do not always induce the changes of kinetic parameters in the same direction [56,57]. Taking into account the facts that the insulin secondary structure changes from almost completely helical to predominant β-sheets [58], and that the hydrophobic core of insulin (B-chain, the residues 11-17 [40]) is exposed to solvent during partial unfolding of the protein (enhanced by NaCl), followed by the formation of oligomers and protofibrils [45,57], it can be…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Las diluciones se realizaron a partir de una solución de 55 % etanol / 10 mM buffer fosfato. Cuanto más concentrados eran los extractos, presentan una mayor reducción en la turbidimetría (casi completa en el caso del meliloto) 20 . En nuestro trabajo, obtuvimos una disminución máxima de la turbidimetría de las fibrillas del 66.61 % para una concentración de 230.77 μg/mL de antocianinas (concentración más alta en este estudio).…”
Section: Ensayos De Anti-agregación/desagregación De La Proteína Amiloide Aβ1-42unclassified
“…19 A number of studies have shown that polyphenolic compounds inhibit the fibril formation. [20][21][22][23][24] The antihypertensive, lipid-lowering, antiobesity, antidiabetic, antiatherosclerotic, antithrombotic, and cardioprotective effects of avocado have been demonstrated in many studies. 16 The avocado fruit phytochemicals also can provide a beneficial nutrition strategy for cancer prevention.…”
mentioning
confidence: 99%